Theories of personality - Hall, Calvin Springer; Lindzey, Gardner; Campbell, John B. (New York : J. Wiley, 1998)
The nature of personality theory. Sigmund Freud's classical psychoanalytic theory. Carl Jung's analytic theory. Social psychological theories: adler, fromm, horney, and sullivan. Erik Erikson and contemporary psychoanalytic theory...
Keywords: Personality; Personality